Sub‐Micrometer Zeolite Films on Gold‐Coated Silicon Wafers with Single‐Crystal‐Like Dielectric Constant and Elastic Modulus. (8th May 2017) - Tiriolo, Raffaele; Rangnekar, Neel; Zhang, Han; Shete, Meera; Bai, Peng; Nelson, John; Karapetrova, Evguenia; Macosko, Christopher W.; Siepmann, Joern Ilja; Lamanna, Ernesto; Lavano, Angelo; Tsapatsis, Michael
Abstract : A low‐temperature synthesis coupled with mild activation produces zeolite films exhibiting low dielectric constant (low‐ k ) matching the theoretically predicted and experimentally measured values for single crystals. This synthesis and activation method allows for the fabrication of a device consisting of a b ‐oriented film of the pure‐silica zeolite MFI (silicalite‐1) supported on a gold‐coated silicon wafer. The zeolite seeds are assembled by a manual assembly process and subjected to optimized secondary growth conditions that do not cause corrosion of the gold underlayer, while strongly promoting in‐plane growth. The traditional calcination process is replaced with a nonthermal photochemical activation to ensure preservation of an intact gold layer. The dielectric constant ( k ), obtained through measurement of electrical capacitance in a metal–insulator–metal configuration, highlights the ultralow k ≈ 1.7 of the synthetized films, which is among the lowest values reported for an MFI film. There is large improvement in elastic modulus of the film ( E ≈ 54 GPa) over previous reports, potentially allowing for integration into silicon wafer processing technology. Abstract : Well‐intergrown and highly b ‐oriented silicalite‐1 films on gold‐coated silicon wafers are obtained. Optimized growth conditions and mild detemplation ensure compatibility with the support. The dielectric constant is measured by using a metal–insulator–metal configuration. For the first time, the films are found to combine ultralow dielectric constant and high mechanical strength, similar to the theoretically predicted values for single‐crystal MFI.